2016
DOI: 10.1097/scs.0000000000002231
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Analysis of the Face

Abstract: Differences of statistical significance were noted in the head and face regions among sexes as well as among Greek and North American Caucasians. With the establishment of facial norms for Greek adults, this study contributes to the preoperative planning as well as postoperative evaluation of Greek patients that are, respectively, scheduled for or are to be subjected to facial reconstructive and aesthetic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 10 publications
3
33
3
1
Order By: Relevance
“…The nose is a very significant part of the face and has its own characteristics. The men's noses were longer and wider, which has been observed before [18]. In our study we confirmed the nose lengthening and extension with age, consistent with published data [29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The nose is a very significant part of the face and has its own characteristics. The men's noses were longer and wider, which has been observed before [18]. In our study we confirmed the nose lengthening and extension with age, consistent with published data [29].…”
Section: Discussionsupporting
confidence: 93%
“…The faces were wider for the men than the women, as has been described before [18]. Differences in the facial widths between the genders were greater in the older adults, independent of the BMI.…”
Section: Discussionsupporting
confidence: 74%
“…Historically, the field of anthropometry, which aims to characterize the physical size, form, and function of humans, has used the top-down approach of naturalistic observation to identify up to 31 different dimensions of face variation, including jaw width, forehead height, and interpupillary distance (see, e.g., Zacharopoulos et al 2016). Over the past three decades, rapid technical developments in face measurement have advanced from laser scanning (e.g., Arridge et al 1985, Hill et al 1997, Vetter & Troje 1997) to high-resolution digital camera capturing (e.g., Hammond & Suttie 2012) combined with specialized face-reconstruction algorithms (e.g., Blanz & Vetter 1999) to accurately render 3D face morphologies for scientific use [e.g., illumination (e.g., Braje et al 1998), viewpoint dependence (e.g., Hill et al 1995, Johnston et al 2013, and identity (e.g., Leopold et al 2001, Troje & Bülthoff 1996] and computer animation.…”
Section: The Human Face Is a Complex High-dimensional Dynamic Informmentioning
confidence: 99%
“…Most female individuals can be classified as leptoprosopic (36.8%) whereas male individuals are mesoprosopic (29.74%) when the overall FI mean is estimated (5). The difference in FI between men and women is also evident in other populations, and this index is usually lower in women than in men (2,16,17).…”
Section: Discussionmentioning
confidence: 99%